Identifying real and perceived barriers to therapeutic education programs for individuals with inflammatory arthritis. Issue 9 (September 2016) - Bain, Lorna; Sangrar, Ruheena; Bornstein, Carolyn; Lukmanji, Sara; Hapuhennedige, Sandani; Thorne, Carter; Beattie, Karen
Abstract Therapeutic Education Programs (TEPs) grounded in self-management principles have been shown to improve quality of life of patients with chronic conditions and reduce patient-related healthcare costs. Though these programs are becoming more readily available, patients often experience barriers in participating. This study sought to identify barriers faced by inflammatory arthritis (IA) patients in attending a TEP and understand how patients overcame perceived barriers. A mixed-method study design was used. Questionnaires were distributed to individuals with IA who were invited to attend a TEP between 2010 and 2013. Respondents were those that chose not to attend (group A), individuals who attended ≤4 of 10 sessions (group B), individuals who attended ≥5 of 10 sessions prior to May 2013 (group C), and individuals who attended ≥5 of 10 sessions from June 2013 to November 2013 (group D). Individuals in group D were also invited to participate in focus groups to discuss how they had overcome perceived barriers. Real barriers identified by individuals in groups A and B included time, distance, and cost associated with attendance. Individuals who overcame perceived barriers (groups C and D) discussed strategies they used to do so. Aspects of the overall program experience and access to clinic and program also contributed to patients being able to overcome barriers. Time, distance, and cost are external barriers that prevented individuals from utilizing self-management education opportunities. These barriers were overcome if and when individuals had resources available to them. Readiness for behavior change also influenced commitment to participate in the program.